(untitled) (Bangladesh Journal of Medical Science, 2023)
Aims: The purpose of this study was to determine the relationship between nurses’ anxiety and depression levels and their compliance with isolation measures during the COVID-19 pandemic. Background: The global COVID-19 pandemic has had severe psychological impacts on nurses. Methods: Following receipt of the requisite approvals, data were collected actively from 289 nurses consenting to participate in the study through an online questionnaire using theinternet/ social media. Results: Mean stress, anxiety, and depression scores were higher among carers for COVID-19 patients than in non-Covidcarers. Analysis revealed significant positive correlation between Isolation Precautions Compliance Scale scores and stress, anxiety, depression, and burnout. Conclusion: Burnout increased while compliance with isolation precautions decreased in this study as stress, anxiety, and depression increased. Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 115-120